Storytelling and User-Generated Content as Marketing Communication Strategies: A Case Study of @beranibackpacker on Instagram - Rofian Dedi Susanto; Rifky Maulana (Jurnal Ilmiah Syi'ar, 2026)
The rapid advancement of digital technology has fundamentally transformed the tourism marketing landscape, shifting paradigms from unilateral broadcasting toward participatory co-creation. To facilitate this, integrating digital storytelling and User-Generated Content (UGC) has become a crucial mechanism for cultivating authentic interactions, a practice notably demonstrated by the travel community Berani Backpacker. Consequently, this study examines the application of these dual instruments as a cohesive marketing communication strategy on Instagram. Moving beyond conventional itinerary promotion, this research explores how the operator commodifies the content creation process through a "full ngonten" ethos. Adopting a descriptive qualitative approach, this single instrumental case study gathered empirical data via netnographic observation and systematic documentation of the @beranibackpacker account. Data were rigorously analyzed using NVivo 14 software through structural coding and thematic mapping. Findings reveal that storytelling is strategically manifested via visual narratives curating an aspirational tourist gaze, affective copywriting commodifying travel experiences, and ephemeral media fostering real-time digital co-presence. Simultaneously, utilizing UGC stimulates a prosumption phenomenon, elevating tourists into decentralized digital creators. This participant-generated media functions as an algorithmic curation mechanism and authentic electronic word-of-mouth (eWOM), significantly reinforcing brand credibility. The seamless synergy between structured narrative scaffolding and organic UGC successfully translates physical tourism into symbolic digital capital. Ultimately, these insights provide theoretical contributions by validating experiential value co-creation, alongside a practical blueprint for optimizing social media architectures within the contemporary attention economy.